Air Curtain Dust Removal Device Design and Dust Prevention Strategy in Heading Face - Xu Huang (Advances in Civil Engineering, 2020)
Dust protection is a safety guarantee of heading face. The previous model of air curtain research was ideal, and the dust removal effect was rarely studied in the actual dust-producing face. This paper presents a method of air curtain dust removal (ACDR) in the actual heading face. The author designed an air curtain dust removal device (ACDRD). The law of total dust concentration, respiratory dust concentration, and respiratory dust ratio is obtained. The minimum outlet airflow velocity is analyzed using the flat-plane injection theory. The effect of the exhaust fan placement on the dust removal effectiveness is examined. Research indicates the following: The airflow speed at the upper, left, and right sides of the ∩-shaped slot is 17.39 m/s, 12.04 m/s, and 13.66 m/s, respectively. The minimum dust removal speed of the air curtain is 5.48 m/s. The total dust concentration is the highest in the spot of roadheader operator, and the concentration of respiratory dust decreases sharply within 20 m. When the indentation air duct is 2.1 m away from the base plate, the dust-proof effect is better. The results can provide theoretical bases and methods for air curtain analysis of the heading face.